Towards a competitive ST system in the defense sector: Air Force case study - Florez Zuluaga, Jimmy Anderson; Molina Carvajal, Luisa Fernanda; Gallego León, Kelly Bermannury (Ingeniería Solidaria, 2021)
Summary: This article describes a diagnostic investigation called, sustainable military science and technology (ST) in Colombian Air Force (FAC), developed in Aerospace Technological Development Centre (CETAD) between 2019 and 2020, which seeks to identify its weaknesses and strengths to achieve a competitive and sustainable ST system according to the National Security needs that enhances national development and achieve technological sovereignty.Problem: Is it possible to implement a sustainable and competitive ST system in the defense sector, that enhances the economic and industrial development of the country?Objective: This research seeks to diagnose the institutional ST system, identifying weaknesses and strengths and proposing strategies to generate a sustainable and competitive ecosystem.Methodology: A comparison was made between relevant bibliography analysis, the national context, and the result of the diagnoses of the ST system.Results: ST system is characterized by a efforts dispersion and a disconnection with the mission objectives and its leaders, however, there is a success case that shows how with a pragmatic orientation to the mission, results can be achieved.Conclusion: It was determined that it is possible to achieve a system that from the sector supports national development, integrating effective marketing and transfer practices and concentrating efforts on the mission.Originality: Through this research, was possible stablish the ST state of Colombian Air Force in order integrate the system capabilities to the missional process.Limitations: The lack of information provided by personal that conform the ST and the lack of knowledge of missionary processes.